Penggunaan Media Pembelajaran Digital Video pada Anak Usia Dini di Kecamatan Kwadungan Kabupaten Ngawi Untuk Peningkatan Pemahaman Banjir - Noor Aulady, Mohamad Ferdaus; Setiyawan, Cikal (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2024)
Flooding is one of the natural disasters that often occurs in various regions in Indonesia. Flood disaster mitigation can be introduced to children in a way that is easily understood by them. The purpose of this research is to introduce the use of digital film learning media for flood disaster mitigation. The selection of digital video media is based on the fact that children can more easily access and understand the content. To determine the initial knowledge through Pre-test and its improvement after the distribution of digital video media through Post-test, researchers in this study used a measuring tool in the form of a questionnaire distributed to 30 respondents. The value of respondents' public knowledge was proven to be higher in the results of data analysis and Wilcoxon test. The results of data analysis where the value of community knowledge who became respondents in this study was rated better and, in the Wilcoxon, test the results obtained <0.05 showed that children were more aware of the existence of flood disasters and their risk factors after seeing digital media learning videos. The development of a flood disaster mitigation programme in the form of digital media learning videos is proven to foster knowledge and attitudes of early childhood to respond to disasters early.